Identifying spatiotemporal variations in four-spot megrim (Lepidorhombus boscii) fishery nurseries to enhance management and stock assessment - Esther Abad; Francisco Izquierdo; Jorge Landa; Francisco Velasco; Manuel Hidalgo; Maria Grazia Pennino (Frontiers in Marine Science)
IntroductionThe identification of recruitment areas and other essential fish habitats of exploited stocks is a fundamental requirement for the development of marine spatial planning and ecosystem conservation measures. Reducing recruitment mortality is particularly relevant on the northern continental shelf of the Iberian Peninsula and is one of the key prerequisites for the future sustainability of trawl fisheries.MethodsIn this study, the distribution of nursery areas of four-spot megrim (Lepidorhombus boscii) was analyzed using time series of scientific bottom trawl survey data to assess whether recruitment areas are persistent over time. Four environmental variables were considered as potential predictors of recruit distribution, as they may influence habitat selection by this species: sea bottom temperature, sea bottom salinity, bathymetry, and sediment type. Additionally in a second stage and based on the spatial findings during this work, the recruitment abundance index within the a4a stock assessment model currently used to provide scientific advice for this species was divided into two spatial areas.ResultsSpatial analyses revealed a specific depth preference for four-spot megrim recruits, with higher abundance in shallower waters, particularly within the 150 to 300 m depth range, respect deeper ones. More importantly, our findings showed significant spatial-temporal variability in four-spot megrim nursery areas. Furthermore, the results of the updated assessment model showed differences in biological reference points (BRPs) compared to the existing model.DiscussionThis suggests that static spatial management approaches may be ineffective due to environmental variability and underscoring the importance of incorporating spatial structure into the assessment process. This approach enables more accurate stock evaluations and more effective, sustainable management, thus laying the groundwork for a potential implementation of spatial stock assessment for this species.